The Impact of Academic Stress on Students' Mental Health: A Qualitative Study of Student Experiences - Insantuan, Baltasar; Sihotang, Hotmaulina; Murniarti, Erni; Buaton, Julisesko (Journal La Sociale, 2026)
This research examines the impact of academic stress on students' mental health, which is caused by high academic demands. Using a qualitative approach and in-depth interviews, the study explored the experiences of 20 students at SMP Budi Mulia Bogor during August-September 2025. The purpose of this study is to identify and analyze how academic stress, such as heavy workloads, pressure to achieve, and academic competition, can become a "silent killer" that erodes students' psychological well-being. The results indicate that high academic stress significantly contributes to increased anxiety, depression, and burnout among students. Implications include sleep disturbances, fatigue, decreased motivation, and withdrawal behavior. Therefore, it is important to create a learning environment that supports students' mental health through proportional time allocation, transparent scheduling, innovative teaching methods, as well as the active role of teachers and parents in supporting students' psychological well-being.